Evaluating the Impact of Lean Innovation Practices on Organizational Agility and Responsiveness - Rafi Farizky (Politeknik Siber Cerdika Internasional, 2024)
This study evaluates the impact of lean innovation practices on organizational agility and responsiveness across the technology, manufacturing, and consumer goods sectors. Using a mixed-methods approach, data were collected from 120 organizations, analyzing key metrics such as time-to-market, responsiveness to customer demands, and operational waste reduction. Findings reveal that lean practices, particularly Kaizen and value stream mapping, significantly enhance organizational agility, with technology firms achieving the highest improvements in time-to-market and adaptability. However, sector-specific challenges, such as fluctuating demand in consumer goods, highlight the need for tailored lean strategies. The results support theories of organizational agility and continuous improvement, underscoring the role of lean practices in enabling companies to respond swiftly to dynamic market conditions. Practical implications suggest that industry leaders adopt balanced approaches to lean implementation, while policymakers could develop frameworks that promote lean practices tailored to different industry demands. Future research could examine lean practices in smaller organizations and explore additional strategies for optimizing agility in complex market environments.